STUDI KELAYAKAN INVESTASI DAN OPTIMALISASI KEUNTUNGAN DEVELOPER DENGAN PROPORSIONAL JUMLAH TIPE RUMAH - Astiah Amir; Dorra Sikhhy (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2016)
Research on Development Projects Griya Mahony aims to determine the feasibility of the investment project in this case the benefits will be achieved. The feasibility study is based on the financial aspectsof using parameter Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR) is calculated based on the length of the installment/credit generate favorable value/ feasible (feasible). For a 10-year installment (NPV Rp.802.618.444, BCR 1.036 and 2.469% IRR), for repayment periods of 15 years (NPV Rp4.208.880.167, BCR and IRR 1,174 5,368%), for repaymentperiods of 20 years ( NPV is Rp7.432.022.615, BCR and IRR 1,285 6.555%), and for the repayment periods of 25 years (NPV Rp10.886.611.347, BCR and IRR 1,388 7.272%). So the value obtained in this project future installments of not less than 10 years and not more than 25-year repayment periods. Having carried out a sensitivity analysis for future installments credit 10 years of investment is not feasible (unfeasible), while for future installments / credit 15 years, a period installment/loan repayment periods of 20 years and credit / 25 years of investment in this project is still feasible. This study was followed by memproporsionalkan number of house types to be produced to obtain the optimal proportion of the number of houses. From these results, the optimal amount that must be built on to three (3) types of housing totaling 76 units, with 80 types of houses as many as 13 units, 65 type of house 29 units, and 45 types of housing as many as 34 units. Gains derived from the proportion of the number of house types are optimal for repayment periods of 10 years of Rp7.162.031.000, for 15year repaymentperiods Rp11.08509 billion, to 20-year repayment periods ofRp15.380.030.000 and to 2-year installment period Rp 19.95799 billion. From the calculation of investment feasibility studies for optimal conditions of house number greater than the condition of houses planned by the developer.